Calcium imparts tolerance to high electrical conductivity in Lisianthus (Eustoma grandiflorum Raf. Shinn.) - López-Pérez Carlos Antonio; Valdez-Aguilar, Luis Alonso; Robledo-Torres Valentín; Mendoza-Villarreal, Rosalinda; Castillo-Gonzalez Ana María (Revista Mexicana de Ciencias Agrícolas, 2018)
It has been reported that calcium (Ca) has a moderating effect on the effects of salinity, and which maintains the integrity of cellular membranes and reduce the loss of potassium (K). Lisianthus is an ornamental plant whose habitat suggests that it can adapt to extreme conditions. This study set out to assess whether the Ca (9 and 13 meq L-1) influences lisianthus tolerance to increased electrical conductivity (EC) (2.5, 4, 6 and 8 dS m-1) in the nutrient solution. The dry weight was reduced when EC 4 dS m-1 regardless of the level of Ca was raised; however, the biomass was recovered when the EC increased to 6 and 8 dS m-1 plants with 13 meq Ca L-1 of plants with extra Ca maintained a greater concentration of photosynthetic pigments when the EC was 6 and 8 dS m-1. Regardless of the concentration of Ca, the net photosynthesis affected EC to decrease when the EC increased to 4 dS m-1. The relative water content (RWC) in young leaves of plants supplemented with additional levels of Ca increased when treated with solutions with EC greater than 4 dS m-1, which was associated with a higher water potential. The concentration of nitrogen, K, Ca and magnesium was affected by the EC but this is recovered with additional Ca. The results indicate that lisianthus high salinity tolerant only if additional quantities are added Ca.